2019
DOI: 10.1136/openhrt-2018-000949
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitive cardiac troponin T as a predictor of efficacy and safety after pulmonary vein isolation using focal radiofrequency, multielectrode radiofrequency and cryoballoon ablation catheter

Abstract: IntroductionMyocardial injury markers such as high-sensitive cardiac troponin T (hs-cTnT) and creatine kinase MB (CK-MB) reflects the amount of myocardial injury with ablation. The aim of the study was to identify the value of myocardial injury markers to predict outcomes after pulmonary vein isolation (PVI) using three different ablation technologies.MethodsConsecutive patients undergoing PVI using a standard 3.5 mm irrigated-tip radiofrequency catheter (RF-group), an irrigated multielectrode radiofrequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Recently Zeljkovic et al 21 reported there was no significant difference in troponin release between patients treated with radiofrequency catheter ablation and cryoballoon ablation. None of the myocardial injury markers were predictive for AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Zeljkovic et al 21 reported there was no significant difference in troponin release between patients treated with radiofrequency catheter ablation and cryoballoon ablation. None of the myocardial injury markers were predictive for AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic and transoesophageal echocardiogram to rule out left atrial (LA) thrombus, to determine LA diameter in the parasternal long axis (PLAX) plane, and left ventricular ejection fraction (LVEF) were performed before every PVI procedure. PVI procedure was performedeither using: (i) focal irrigated‐tip radiofrequency (RF) catheter (RF‐group) in combination with a 3D electroanatomical mapping systems (either CARTO3, Biosense Webster, or NavX, Abbott) as described in detail previously 13 , 14 ; (ii) using the 2nd‐generation cryoballoon (Arctic Front Advance 28 mm Medtronic Inc.,) ablation (CB‐group) as described in detail previously. 13 , 14 …”
Section: Methodsmentioning
confidence: 99%
“…PVI procedure was performedeither using: (i) focal irrigated‐tip radiofrequency (RF) catheter (RF‐group) in combination with a 3D electroanatomical mapping systems (either CARTO3, Biosense Webster, or NavX, Abbott) as described in detail previously 13 , 14 ; (ii) using the 2nd‐generation cryoballoon (Arctic Front Advance 28 mm Medtronic Inc.,) ablation (CB‐group) as described in detail previously. 13 , 14 …”
Section: Methodsmentioning
confidence: 99%
“…3 Nevertheless, effort to predict the recurrence of AF is an exciting development. [4][5][6][7] It enables physicians to stratify the risk of AF recurrence and weight the risk and benefit on the patients before performing catheter ablation.…”
Section: Introductionmentioning
confidence: 99%